2013
DOI: 10.1097/ico.0b013e3182a02ddb
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Refractive and Topographic Changes in Early and Advanced Keratoconic Eyes Undergoing Corneal Collagen Crosslinking

Abstract: Corneal CXL is more effective in improving the refractive and topographical parameters at 1 year when it is performed early in the course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 19 publications
2
31
0
3
Order By: Relevance
“…Among these 23 trials, 4 were RCTs9101114, 11 were prospective controlled studies715161718192021222324, and 8 were retrospective studies1225262728293031 (Table 1). A total of 1171 participants with 1557 affected eyes were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 23 trials, 4 were RCTs9101114, 11 were prospective controlled studies715161718192021222324, and 8 were retrospective studies1225262728293031 (Table 1). A total of 1171 participants with 1557 affected eyes were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] With growing evidence of the efficacy and safety of CXL, some doctors seem to be divided between those who believe the procedure should be reserved for eyes that demonstrate progression and those who believe it should be performed at the time of diagnosis, especially in some cases at high risk of progress such as young patients. 15,16 After CXL, several studies show stabilization and/or improvement in topographic data, 14,17,18 but other authors have reported cases of late progression, after 5 years of treatment. 14 Thus, with the advent of CXL, an accurate corneal assessment using objective parameters such as keratometry and pachymetry has become a necessary part of the preoperative and postoperative evaluation to allow meaningful follow-up of the procedure.…”
Section: Discussionmentioning
confidence: 96%
“…14 Thus, with the advent of CXL, an accurate corneal assessment using objective parameters such as keratometry and pachymetry has become a necessary part of the preoperative and postoperative evaluation to allow meaningful follow-up of the procedure. [12][13][14][15][16][17][18] Other clinical applications such as postsurgical follow-up of refractive surgery could be cited as examples for the necessity of accurate interpretation of corneal measurements. 11,19,20 The Pentacam is a noninvasive anterior segment tomographer that uses a rotating Scheimpflug camera.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to halting the ectatic process [22][23][24], CXL results in decrease of corneal curvature irregularity, manifested as central anterior corneal flattening [25,26]. In other words, the overall increase in corneal biomechanics (the stiffening effect over the entire cornea) is invariably accompanied by corneal curvature reduction [27][28][29][30][31].…”
Section: Corneal Collagen Cross-linking For Presbyopia: a Novel Approachmentioning
confidence: 98%